2021
DOI: 10.3390/su132111659
|View full text |Cite
|
Sign up to set email alerts
|

Traces of Honeybees, Api-Tourism and Beekeeping: From Past to Present

Abstract: Throughout history, honey has been used for many different purposes and due to its medicinal properties, has been one of the products marketed by traders. The figure of the bee first appeared in drawings on rock with the history of humanity, then on statues, as a logo, on money or stamps, and also in movies. Beekeeping museums, which present the historical process of beekeeping, also reflect an important culture with their ancient hives, documents, beekeeping materials, and historical antiquities. The contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Basically, honey bees are provided with all other nutrients, including carbohydrates, from nectar and protein from pollen. Plant populations and productivity in these populations are affected by many factors such as climate change, intensification of agricultural areas, landscape changes and atmospheric pollutants [1][2][3][4][5]. Ghosh et al (2020) showed that the pollen preference of colonies can vary depending on the protein content of the pollen, and bees prefer floral sources with high nutritional content [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, honey bees are provided with all other nutrients, including carbohydrates, from nectar and protein from pollen. Plant populations and productivity in these populations are affected by many factors such as climate change, intensification of agricultural areas, landscape changes and atmospheric pollutants [1][2][3][4][5]. Ghosh et al (2020) showed that the pollen preference of colonies can vary depending on the protein content of the pollen, and bees prefer floral sources with high nutritional content [6].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, honey bees are provided with all other nutrients, including carbohydrates, from nectar and protein from pollen. Plant populations and productivity in these populations are affected by many factors such as climate change, intensification of agricultural areas, landscape changes and atmospheric pollutants [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The honey bee has been part of human culture since ancient times and its products have an extensive history of use (Topal et al 2021). Although multiple investigations focused on the honey bee microbiota (Zheng et al 2018), several studies have examined the microbiological communities of bee products.…”
Section: Discussionmentioning
confidence: 99%
“…A lion at the portal of a Gothic cathedral Besides provisioning and regulating ecosystem services, honey bees and beekeeping can also be linked to cultural services. Among them, the best-known examples are recreational/educational activities, such as api-tourism, a form of agro-tourism related to beekeeping, which includes a number of beekeeping-oriented activities (e.g., visits to apiaries, bee museums, honey tasting, and apitherapy), and art inspiration [135,186,187].…”
Section: The Role Of the Honey Bee In The Ecosystem Of The Symbolic Traditionmentioning
confidence: 99%
“…Apitherapy is increasingly becoming the basis of api-tourism, i.e., a kind of tourism focused on physical health and well-being [ 135 , 136 ]. Kotova and Lesnikov [ 137 ] discussed and marked the symbiosis of apitherapy and tourist-recreational resources in health tourism as a factor of effective post-COVID-19 health.…”
Section: Use Of Bee Products As Raw Materials and Medicinal Resourcesmentioning
confidence: 99%